A preliminary survey on the indigenous utilization and assessment of nutritional value of agihis in Brgy. Cabadiangan, Himamaylan City, Negros Occidental - Tugahan, Angelo Garibay (2012.)
A freshwater shellfish locally known as "agihis" is being utilized by people living in Sitio Palayan, Brgy. Cabadiangan, Himamaylan City, Negros Occidental as food.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Agihis shellfish; Wedged-clam.